Efficacy of antimicrobial treatments against Salmonella enterica on pork and Campylobacter jejuni on poultry - González Sánchez, Sara Victoria, author; Belk, Keith E., advisor; Geornaras, Ifigenia, advisor; Delmore, Robert J., committee member; Weir, Tiffany L., committee member (Colorado State University. Libraries, 2020)
Two studies were conducted to evaluate efficacy of antimicrobial treatments against Salmonella enterica on pork and Campylobacter jejuni on poultry. The first study was conducted to (i) evaluate decontamination efficacy of six chemical treatments when applied to pork jowls inoculated with Salmonella enterica and (ii) determine the antimicrobial efficacy of the test solutions against a high and low inoculum level of Salmonella. Chilled pork jowls were cut into 10 × 5 × 1 cm portions and were surface-inoculated on the skin side with a mixture of six S. enterica serotype strains of swine origin. The inoculation levels targeted were 6 to 7 log CFU/cm2 (high) and 3 to 4 log CFU/cm2 (low). Following inoculation, samples were left untreated (control) or were treated by spray application (10 s, 18 to 19 psi, 1.0 gpm flow rate) with water, a proprietary blend of sulfuric acid and sodium sulfate (SSS, pH 1.2), formic acid (1.5%), peroxyacetic acid (PAA, 400 ppm), PAA (400 ppm) acidified with acetic acid (1.5%), PAA (400 ppm) acidified with formic acid (1.5%), or PAA (400 ppm) acidified with SSS (pH 1.2). Samples were analyzed for inoculated Salmonella counts immediately after treatment application (0 h) and after 24 h of refrigerated (4°C) storage. Overall, all seven spray treatments were effective (P < 0.05) at reducing the high and low Salmonella inoculation levels. At the high inoculum level (6.2 log CFU/cm2), pathogen counts ranged from 5.4 (water; 0.8 log CFU/cm2 reduction) to 4.3 (PAA acidified with SSS; 1.9 log CFU/cm2 reduction) log CFU/cm2 for samples analyzed immediately after spray treatment. Salmonella counts obtained at the 0-h sampling time for treated samples inoculated at the low inoculum level (3.5 log CFU/cm2) ranged from 2.8 (water; 0.7 log CFU/cm2 reduction) to 1.8 (PAA acidified with SSS; 1.7 log CFU/cm2 reduction) log CFU/cm2. Thus, regardless of inoculum concentration, similar reductions of Salmonella populations were obtained immediately following treatment application (0 h). For the high inoculation level, Salmonella counts of samples analyzed after 24 h of refrigerated storage were, in general, similar (P ≥ 0.05) to the counts of the corresponding treatment at 0 h. However, for the low inoculation level, pathogen counts of jowls treated with SSS, formic acid, or PAA acidified with formic acid, and held at 4°C for 24 h, were 0.6 log CFU/cm2 lower (P < 0.05) than the 0-h counts of the corresponding treatment. Regardless of inoculation level and sampling time, no (P ≥ 0.05) differences in efficacy were obtained between PAA on its own and any of the acidified PAA treatments evaluated. The second study was conducted to (i) evaluate decontamination efficacy of five chemical treatments when applied to chicken wings inoculated with Campylobacter jejuni and (ii) determine antimicrobial efficacy of the treatments as a result of applying test solutions by immersion or spraying. Skin-on chicken wings were surface-inoculated with a six-strain mixture of C. jejuni of poultry origin. The target inoculation level was 3 to 4 log CFU/mL of wing rinsate. Following inoculation, samples were left untreated (control) or were treated by immersion (500 mL solution per wing; 5 s) or spray application (10 to 12 psi; 4 s) with water, SSS (pH 1.2), formic acid (1.5%), PAA (550 ppm), PAA (550 ppm) acidified with SSS (pH 1.2), or PAA (550 ppm) acidified with formic acid (1.5%). Samples were analyzed for C. jejuni counts immediately after treatment application (0 h) and following 24 h of storage (4°C). All five acid treatments evaluated in this study were effective (P < 0.05) at reducing the initial inoculated (3.9 log CFU/mL) C. jejuni populations on chicken wings, regardless of the antimicrobial treatment application method. Pathogen counts for samples spray-treated with one of the chemical solutions and analyzed immediately (0 h) after treatment ranged from 3.4 (SSS; 0.5 log CFU/mL reduction) to 2.7 (PAA acidified with formic acid; 1.2 log CFU/mL reduction) log CFU/mL. When the chemical treatments were applied by immersion, C. jejuni counts of 2.2 (SSS; 1.7 log CFU/mL reduction) to 1.7 (PAA, and PAA acidified with SSS; 2.2 log CFU/mL reduction) log CFU/mL were obtained for wings analyzed at the 0-h sampling time. The PAA and acidified PAA treatments were equally (P ≥ 0.05) effective at reducing initial C. jejuni populations, regardless of treatment application method. However, following refrigerated storage, samples treated with SSS- or formic acid-acidified PAA had lower (P < 0.05) pathogen counts than those that had been treated with the non-acidified PAA treatment. Overall, findings of the two studies should be useful to the pork and poultry industries as they consider new interventions against Salmonella and Campylobacter contamination on pork and chicken parts, respectively.
Keywords: pork; peroxyacetic acid; antimicrobials; poultry; Campylobacter; Salmonella